Creating a model to predict time intervals from induction of labor to induction of anesthesia and delivery to coordinate workload. (February 2021) - Warner, L.L.; Hunter Guevara, L.R.; Barrett, B.J.; Arendt, K.W.; Peterson, A.A.; Sviggum, H.P.; Duncan, C.M.; Thompson, A.C.; Hanson, A.C.; Schulte, P.J.; Martin, D.P.; Sharpe, E.E.
Highlights: Labor induction start times influence when patients receive analgesia and deliver. Optimal anesthesia and delivery times are when the most resources are available. Modeling was used to estimate the optimal start time for induction of labor. 2 am induction (nulliparous women) results in optimal analgesia and delivery timing. 5 am induction (parous women) results in optimal analgesia and delivery timing. Abstract: Background: Induction of labor continues to become more common. We analyzed induction of labor and timing of obstetric and anesthesia work to create a model to predict the induction-anesthesia interval and the induction-delivery interval in order to co-ordinate workload to occur when staff are most available. Methods: Patients who underwent induction of labor at a single medical center were identified and multivariable linear regression was used to model anesthesia and delivery times. Data were collected on date of birth, race/ethnicity, body mass index, gestational age, gravidity, parity, indication for labor induction, number of prior deliveries, time of induction, induction agent, cervical dilation, effacement, and fetal station on admission, date and time of anesthesia administration, date and time of delivery, and delivery type. Results: A total of 1746 women met inclusion criteria. Associations which significantly influenced time from induction of labor to anesthesia and delivery included maternal age (anesthesia P <0.001, delivery P =0.002), body mass index (both P <0.001), prior vaginal delivery (both P <0.001), gestational age (anesthesia P <0.001, delivery P <0.018), simplified Bishop score (both P <0.001), and first induction agent (both P <0.001). Induction of labor of nulliparous women at 02:00 h and parous women at 04:00 or 05:00 h had the highest estimated probability of the mother having her first anesthesia encounter and delivering during optimally staffed hours when our institution's specialty personnel are most available. Conclusions: Time to obstetric and anesthesia tasks can be estimated to optimize induction of labor start times, and shift anesthesia and delivery workload to hours when staff are most available.